Association of hospital admission service structure with early transfer to critical care, hospital readmission, and length of stay. Issue 10 (19th April 2016) - Smith, G. Randy; Ma, Madeleine; Hansen, Luke O.; Christensen, Nick; O'Leary, Kevin J.
Abstract : BACKGROUND: Hospital medical groups use various staffing models that may systematically affect care continuity during the admission process. OBJECTIVE: To compare the effect of 2 hospitalist admission service models ("general" and "admitter‐rounder") on patient disposition and length of stay. DESIGN: Retrospective observational cohort study with difference‐in‐difference analysis. SETTING: Large tertiary academic medical center in the United States. PARTICIPANTS: Patients (n = 19, 270) admitted from the emergency department to hospital medicine and medicine teaching services from July 2010 to June 2013. INTERVENTIONS: Admissions to hospital medicine staffed by 2 different service models, compared to teaching service admissions. MEASUREMENTS: Incidence of transfer to critical care within the first 24 hours of hospitalization, hospital and emergency department length of stay, and hospital readmission rates ≤30 days postdischarge. RESULTS: The change of hospitalist services to an admitter‐rounder model was associated with no significant change in transfer to critical care or hospital length of stay compared to the teaching service (difference‐in‐difference P = 0.32 and P = 0.87, respectively). The admitter‐rounder model was associated with decreased readmissions compared to the teaching service on difference‐in‐difference analysis (odds ratio difference: −0.21, P = 0.01). Adoption of the hospitalist admitter‐rounder model was associated with an increased emergency department length of stay compared to the teaching service (difference of +0.49 hours, P < 0.001). CONCLUSIONS: Rates of transfer to intensive care and overall hospital length of stay between the hospitalist admission models did not differ significantly. The hospitalist admitter‐rounder admission service structure was associated with extended emergency department length of stay and a decrease in readmissions. Journal of Hospital Medicine 2016;11:669–674. © 2016 Society of Hospital Medicine